Trilateration‐based indoor localization engineering technique for visible light communication system. (6th April 2020) - Naz, Ayesha; M. Asif, Hafiz; Umer, Tariq; Ayub, Shahid; Al‐Turjman, Fadi
Summary: This article is aimed at designing positioning system using visible light communication technology by incorporating three different diversity schemes, namely, transmit diversity (TD), receive diversity (RD), and angle diversity. For the TD, multiple transmitters with single receiver (MISO) is used to obtain the target location using frequency division multiplexing (FDM) and variable phase approach. To deploy RD, the proposed system comprises multiple receivers and single transmitter (SIMO). Only one transmitter's absolute coordinates are required to obtain the location coordinates of optical receivers. FDM and time division multiplexing access schemes have been utilized to transmit the unique signals by light‐emitting diodes (LEDs). To implement angle diversity, orientation of transmitter and receiver is considered for positioning purposes. Under this environment, there is no constraint for the LEDs to be installed on ceiling; they can be at any point within the room or at different heights. The information regarding spherical coordinates (representing the orientation) of LEDs (single or multiple) is used to determine the coordinates or the orientation of receiver having multiple or single photodiodes, respectively. Under multiple orientations, this system is analyzed with both scenarios, that is, MISO and SIMO.